2022
DOI: 10.5194/bg-2022-1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The soil carbon erosion paradox reconciled

Abstract: Abstract. The acceleration of erosion, transport and burial of soil organic carbon (C) in response to agricultural expansion represents a significant perturbation of the terrestrial C cycle. Recent model advances now enable improved representation of the relationships between sedimentary processes and C cycling and this has led to substantially revised assessments of changes in land C as a result of land cover and climate change. However, surprisingly a consensus on both the direction and magnitude of the eros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Kühn et al, 2017;Von Suchodoletz et al, 2019). Small Many studies emphasise, that waterlogging of soils at sediment depositional sites, reduces the soil microbial activity, stabilising SOC and limiting organic matter decomposition rates, affecting SOC resources (T. Li et al, 2019;Stallard, 1998;Świtoniak et al, 2015;Van Oost et al, 2007;Van Oost & Six, 2022;Zhang et al, 2016). Meersmans et al (2008) demonstrated that, in Flanders (Belgium), a higher SOC content coincides with soils of waterlogged areas (depressions areas) because of limitation of the SOC oxidation.…”
Section: Soil Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kühn et al, 2017;Von Suchodoletz et al, 2019). Small Many studies emphasise, that waterlogging of soils at sediment depositional sites, reduces the soil microbial activity, stabilising SOC and limiting organic matter decomposition rates, affecting SOC resources (T. Li et al, 2019;Stallard, 1998;Świtoniak et al, 2015;Van Oost et al, 2007;Van Oost & Six, 2022;Zhang et al, 2016). Meersmans et al (2008) demonstrated that, in Flanders (Belgium), a higher SOC content coincides with soils of waterlogged areas (depressions areas) because of limitation of the SOC oxidation.…”
Section: Soil Typesmentioning
confidence: 99%
“…Burial of SOC in colluvial sediments at depositional sites enhances stabilisation and sequestration of SOC and reduces CO 2 fluxes from the soil to the atmosphere (Berhe et al, 2007;Borrelli et al, 2018;Chaopricha & Marin-Spiotta, 2014;Cheng et al, 2010;Lal & Pimentel, 2008;Stallard, 1998;Van Oost et al, 2007). The need to quantify which part of eroded SOC from soils is buried in sedimentary environments is emphasised in order to better assess terrestrial SOC dynamics and terrestrial carbon storage at large scales (Borrelli et al, 2018;Van Oost & Six, 2022).…”
mentioning
confidence: 99%
“…For example, some used soil-centred approaches, upscale results from plots or small catchments via parsimonious modelling approaches (Naipal et al, 2018; van Oost et al, 2007; Wang et al, 2017), while others uses sediment-centred approaches estimating erosion induced changes in C cycling from the sediment fluxes measured in macroscale river systems (Smith et al, 2001; Lal, 2003). Overall it can be concluded that an accurate global estimate it is currently not possible due to a lack in data to account for small scale dynamics of lateral soil fluxes and also a lack in process understanding while transporting carbon rich sediment from the hillslope into the oceans (Van Oost and Six, 2022).…”
Section: Biogeochemical Cycling and Soil Erosionmentioning
confidence: 99%